Reimagining Language. Issue 7 (23rd June 2022) - Cohn, Neil; Schilperoord, Joost
Abstract: Since its inception, the study of language has been a central pillar to Cognitive Science. Despite an "amodal view, " where language is thought to "flow into" modalities indiscriminately, speech has always been considered the prototypical form of the linguistic system. However, this view does not hold up to the evidence about language and expressive modalities. While acknowledgment of both the nonvocal modalities and multimodality has grown over the last 40 years in linguistics and psycholinguistics, this has not yet led to a necessary shift in the mainstream linguistic paradigm. Such a shift requires reconfiguring models of language to account for multimodality, and demands a different view on what the linguistic system is and how it works, necessitating a Cognitive Science sensitive to the full richness of human communication.